2016
DOI: 10.4102/hsag.v21i0.935
|View full text |Cite
|
Sign up to set email alerts
|

Has the increase in the availability of generic drugs lowered the price of cardiovascular drugs in South Africa?

Abstract: Background: This research focuses on pharmaceutical competition in South Africa where concurrent pricing legislation is being implemented without monitoring the consequences on generic drug competition and usage.Objective: To examine the relationship between originator drug prices and the number of generic brands within the cardiovascular class of drugs and to compare South African prices with international reference prices.Method: Data on private sector drug prices was sourced from the South African Medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Directly after the introduction in 2004 of the SEP the difference between the price of the originator molecule and their cheapest generic showed a 11.1 fold increase in South Africa, in line with Cameron and Laing (2010) [25] suggestion for LMICs. Bangalee, et al revealed in their study on cardiovascular drugs a 40% difference in prices of generics against the branded versions, [7] and this is confirmed in the pre 2004 comparative in this study (42.9%). This study further suggests that the introduction of the SEP increased this differential, at least in the global core basket, to 111%.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Directly after the introduction in 2004 of the SEP the difference between the price of the originator molecule and their cheapest generic showed a 11.1 fold increase in South Africa, in line with Cameron and Laing (2010) [25] suggestion for LMICs. Bangalee, et al revealed in their study on cardiovascular drugs a 40% difference in prices of generics against the branded versions, [7] and this is confirmed in the pre 2004 comparative in this study (42.9%). This study further suggests that the introduction of the SEP increased this differential, at least in the global core basket, to 111%.…”
Section: Discussionsupporting
confidence: 79%
“…This supports the observation by Bangalee and Suleman (2015) that originator companies do not engage in price competition. [7] This may also provide a reason for eight (8) of the fifty (50) originator molecules being withdrawn after 2004.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 2 ] The loss of benefits to consumers resulting from the high levels of discounting and payment of incentives within the pharmaceuticals supply chain had raised serious concerns in the National Department of Health and made it difficult to determine the true price of a medicine. [ 3 ] The single exit price (SEP) regulation, first introduced in 2004 for all medicines in the private sector, is an example of SA’s attempt to control prices and improve pricing transparency in the supply chain. The SEP, which is a composite of the ex-manufacturer’s price, logistics fee and value added tax (VAT), standardised in SA at 14%, mandated that manufacturers sell their products at one price to all their customers (other than the State), regardless of the nature of the customer’s order size and consumption levels.…”
mentioning
confidence: 99%